Diagnosing the Philippine economy toward inclusive growth - Canlas, Dante B.; Khan, Muhammad Ehsan; Zhuang, Juzhong..; Asian Development Bank.; iGLibrary (online resource). (London Published for the Asian Development Bank by Anthem Press, 2009)
'Diagnosing the Philippine Economy' describes the conditions that depress economic growth in the Philippine economy and their causes and potential solutions.
Diagnosing the philippine economy : toward inclusive growth -- Foreword -- Preface -- Contributors -- Abbreviations and Acronyms -- Contents -- 1. Introduction -- Part A: Overview and Synthesis -- 2. Development Performance and Policy -- 3. Critical Constraints to Growth and Poverty Reduction -- Part B: Background Studies -- 4. Macroeconomic Management -- 5. Trade, Investments, and Domestic Production -- 6. Infrastructure -- 7. Human Capital -- 8. Equality and the Social Sector -- 9. Poverty Reduction: Trends, Determinants, and Policies -- 10. Governance, Institutions, and Political Economy -- Index.
A copublication of the Asian Development Bank and Anthem Press.
Includes bibliographical references and index.
Electronic Reproduction.
Keywords: Economic development -- Philippines; Electronic books; Philippines -- Economic conditions